Accounting and analytical support of the marketing of the commission operation of the trade enterprises - Resler, Maryna (Technology audit and production reserves, 2018)
The object of research is commission operations of trade enterprises. In the course of research of scientific works of economists, devoted to the problems of accounting and analytical support of marketing, commission operations of trade enterprises used the methods of analysis and synthesis. And to determine the industry problems of accounting and cost analysis, induction and deduction methods were used. In the course of the study, methods of comparison and analogy were used when analyzing the experience of accounting and cost analysis and marketing risks. And in the process of analyzing the order of formation of the accounting and analytical system of enterprises, abstraction and concretization methods were used. The theoretical research was applied in the process of deepening the interpretation of the essence of the terms «trade» and «commission trade». It should be noted that the approach proposed in the work has a number of features for accounting and analytical support for managing marketing commission operations of trade enterprises. This approach should be considered as accounting and analysis subsystems. This is due to the fact that the distribution proposed in the work makes it possible to avoid risks in trading activities. It is the accounting and analysis subsystems that provide complete accounting and analytical information. It is shown that an important point in trading activity is taking into account the views of consumers. The author agrees with the opinion of scientists who offer to take into account corporate information and are increasingly aware of the extent to which the functional areas of marketing and supply chains are becoming increasingly integrated. It is shown that functional integration provides for the coordination of activities oriented to supply and demand, and theoretically provides for the creation of two interrelated advantages for consumers: reduction of the marketing risk of buying and, ultimately, a higher level of consumer brand. This ensures the possibility of obtaining the necessary information for accounting and analytical support for marketing commission operations of trading activities.